Design criteria for the optimal sizing of integrated photovoltaic-storage systems. (15th April 2018) - Bendato, Ilaria; Bonfiglio, Andrea; Brignone, Massimo; Delfino, Federico; Pampararo, Fabio; Procopio, Renato; Rossi, Mansueto
Abstract: The paper aims at presenting a methodology to choose the proper sizing of an integrated Photovoltaic unit and a storage architecture starting from the knowledge of the load and solar irradiance time profiles. To do this, first a simple logic to manage the charging/discharging of the storage is proposed, then the function representing the overall cost during the whole life of the system is derived. The computation of the cost function for different photovoltaic and storage sizes allows finding the best sizing of the system. Finally, a thorough economic analysis is conducted to provide criteria to check whether the investment is economically advantageous. This is done considering the impact of the economic variables which are more influential on the investment key assessment parameters. The proposed methodology has been validated in different realistic test cases against the results provided by an energy management system, showing an excellent agreement between the approaches. Moreover, the economic analysis has been applied to four realistic situations in order to tailor the microgrid components ratings on the specific test case. Highlights: Optimal sizing of integrated PV-Storage solutions. Integrated PV-Storage economical sustainability assessment. Application of the proposed tool in four realistic scenarios to choose the proper PV and storage ratings. Methodology applicable to define target prices for PV and storage to make to solution competitive.